ELICITATION TECHNIQUES IN CLASSROOM INTERACTION USED BY ENGLISH TEACHERS AT SMAN 1 2x11 KAYUTANAM - Mellati Mandasari; Hermawati Syarif; Refnaldi Refnaldi (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2019)
This study aims to explain the elicitation techniques teachers use to interact in the classroom. This research is descriptive research. The subjects of the study were English teachers at SMAN 1 2x11 Kayutanam. The data were collected using video recordings and observations in four different classes. Conversation analysis is used to analyze and classify data. The research findings show that there are five elicitation techniques used by teachers. The technique is to ask using pictures, texts, dialogues, body language and techniques designed by the teacher himself. Asking to use dialogue is a technique most often used by teachers to ask students. In addition, inquiring using body language is very rarely used by teachers. In the use of elicitation techniques, teachers use several types of questions. The questions consist of yes / no questions, closed questions and open questions. In its use, English teachers ask more yes / no questions and closed questions, while open questions are rarely used. Student responses to elicitation techniques used by teachers are dominated by simple or short answers. Based on the above findings, it can be concluded that teachers tend to use one same elicitation technique at each meeting so that the process of interaction in the classroom is still dominated by the teacher.